Composition, structure, and physicochemical characteristics of pigeon pea (Cajanus cajan) starches from Indonesia - Nur Rohmah Lufti A'yuni; Yustinus Marsono; Djagal Wiseso Marseno; Priyanto Triwitono (Society for Indonesian Biodiversity, 2021)
Abstract. A’yuni NRL, Marsono Y, Marseno DW, Triwitoyo P. 2021. Composition, structure, and physicochemical characteristics of pigeon pea (Cajanus cajan) starches from Indonesia. Biodiversitas 22: 3430-3439. Information on the characteristics of pigeon pea (Cajanus cajan (L.) Millsp.) starch would provide a scientific basis for developing its application. However, data about characteristics of pigeon pea starch, especially from the Southeast Asia region, has been limited. This study determined the composition, structure, and physicochemical characteristics of pigeon pea starches from three different Indonesian regions, i.e., Bali, Yogyakarta, and West Nusa Tenggara (NTB). We also investigated the potential application of Indonesian pigeon pea starches. Pigeon pea starch was extracted using a wet method, and then pigeon pea starch was characterized. The yield of pigeon pea starches ranged from 29.83-31.68%. Pigeon pea starches showed a significant difference (P<0.05) in amylose content (54.74-58.51%), relative crystallinity (24.20-28.97%), water-binding capacity (0.70-0.76 g/g), oil binding capacity (0.55-0.58 g/g), swelling power (13.19-14.52 g/g), and solubility (9.48-11.15%). The pasting properties (except for final viscosity) and thermal properties (except for onset temperature and gelatinization enthalpy) differed significantly. Granules of pigeon pea starch were oval to elliptical, with a mean granule diameter of 18.41-19.98 µm. According to X-ray diffraction patterns, pigeon pea starches showed CA type, contained orthorhombic and hexagonal crystals. Pigeon pea starches also showed the same FTIR spectra. The results revealed that the differences in pigeon pea growing locations affect pigeon pea starch's composition and physicochemical properties. The highest amylose content and lowest relative crystallinity were found in Yogyakarta pigeon pea starch. In the future, our findings could be used to develop pigeon pea starch for various food applications.